2023
DOI: 10.1111/acer.15095
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal examination of high‐risk drinking contexts: Daytime drinking, pregaming, and drinking games linked to high‐risk alcohol use and negative consequences in young adults

Abstract: Background The contexts in which young adults drink alcohol play a salient role in alcohol‐related outcomes and negative consequences at an event‐level, but less is known about longitudinal risks. We collected longitudinal monthly data across 2 years on (a) daytime drinking, (b) pregaming/pre‐partying, and (c) playing drinking games. We then examined associations between drinking in these contexts and within‐person variability in alcohol consumption, consequences, and simultaneous alcohol and marijuana (SAM) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…This finding suggests that college students who engage in FAD-intoxication may be at increased risk of future alcohol use. This is consistent with our hypothesis and in alignment with the previous literature illustrating that enhancement and coping drinking motives longitudinally anticipate alcohol use (Irizar et al, 2021; Stevenson et al, 2019) Moreover, our finding is consistent with prior work demonstrating that students who engage in drinking behaviors that facilitate rapid and intense alcohol consumption (e.g., drinking games, pregaming) are more likely to report higher levels of subsequent alcohol use compared to those who do not follow this drinking pattern (Graupensperger et al, 2023). Last, our results align with Glassman et al (2018) findings that targeting FAD via a messaging-based intervention leads to decreases in future alcohol use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding suggests that college students who engage in FAD-intoxication may be at increased risk of future alcohol use. This is consistent with our hypothesis and in alignment with the previous literature illustrating that enhancement and coping drinking motives longitudinally anticipate alcohol use (Irizar et al, 2021; Stevenson et al, 2019) Moreover, our finding is consistent with prior work demonstrating that students who engage in drinking behaviors that facilitate rapid and intense alcohol consumption (e.g., drinking games, pregaming) are more likely to report higher levels of subsequent alcohol use compared to those who do not follow this drinking pattern (Graupensperger et al, 2023). Last, our results align with Glassman et al (2018) findings that targeting FAD via a messaging-based intervention leads to decreases in future alcohol use.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, there is empirical support for risky drinking behaviors predicting future alcohol use and negative consequences. Specifically, Graupensperger et al (2023) found that participating in drinking behaviors that facilitate rapid and intense alcohol consumption (e.g., drinking games, pregaming) positively associates with same-month alcohol consumption and related negative consequences and predicts future hazardous drinking at the within-person level. Importantly, to allow enough time for attitudes and beliefs related to risky drinking behaviors to shift, longer time between assessments (e.g., several weeks) may be preferable to shorter assessment intervals (e.g., daily).…”
Section: Fad-intoxication As a Predictor Of Alcohol-related Constructsmentioning
confidence: 99%